The Efficacy and Safety Profile of Generic Intravenous Levetiracetam in a Real-World Setting - Preechaya Ruangritkul, MSc; Siriporn Tiamkao, MD; Nanthaphan Chainirun, MSc; Sineenard Pranboon, MSc; Somsak Tiamkao, MD; Kittisak Sawanyawisuth, MD; Sittichai Khamsai, MD (Elsevier, 2021)
ABSTRACT: Background: There are 3 main epileptic conditions in hospital settings that may require intravenous antiepileptic treatment: status epilepticus, acute repetitive convulsive seizures, and postoperative seizures. Generic intravenous levetiracetam (IV LEV) (Focale; Great Eastern Drug Co, Bangkok, Thailand), has been reported to have comparable efficacy to original IV LEV for treating status epilepticus and acute repetitive convulsive seizures in a randomized controlled trial. At present, there are limited data on the efficacy and tolerability of generic intravenous LEV in real-world situations. Objective: This study aimed to evaluate the clinical outcomes of generic IV LEV in a real-world setting. Methods: A retrospective study and analyses were conducted. All adult patients who used IV LEV at University Hospital, Khon Kaen University, Thailand from June 1, 2019, until February 15, 2020, were included. Data were analyzed and reported in terms of the efficacy and tolerability of generic IV LEV. Results: Ninety-three patients received IV LEV by 3 indications: status epilepticus, acute repetitive convulsive seizures, and postoperative seizures. The proportions of these 3 indications were 41.94% (39 patients), 9.67% (9 patients), and 48.39% (45 patients), respectively. The average seizure control rate at 24 hours was 89.25%. The seizure control rate was significantly higher in the acute repetitive convulsive seizures and postoperative seizure groups than in the status epilepticus group when generic IV LEV was given as the first-line treatment (75.00%; 88.37% vs 50.00%; P 0.035). The average length of hospital stay was 18.24 (25.40) days. There was no significant discharge status among the 3 groups (P = 0.348). Moreover, the average mortality rate was 5.38%. Side effects were reported in 14 patients (15.05%). The 2 most common side effects were vomiting and bronchospasm (3 patients; 3.22%). There were 10 patients with uncontrolled seizures at 24 hours (10.75%). The only factor associated with uncontrolled seizures at 24 hours was a history of epilepsy. The uncontrolled seizure group had a higher proportion of epilepsy patients than the seizure-controlled group (70.00% vs 33.73%; P = 0.037). Poor discharge status (not improved/death) was 18.28% (17 patients). There was no significant factor between those with an improved or poor discharge status. Conclusions: Generic IV LEV was effective and relatively well tolerated in the 3 clinical settings (ie, status epilepticus, acute repetitive convulsive seizures, and postoperative seizures). Further clinical data are still required to confirm the results of this study.(Curr Ther Res Clin Exp. 2022; 83:XXX-XXX)